LIVER DISEASES WITH ISOLATED CORE ANTIBODY (Anti-HBc) TO HEPATiTiS B VIRUS - Abdullah SONSUZ; Hakan ŞENTÜRK; Sebati ÖZDEMİR; Sait KARAKURT; Perihan AKIN; Muzaffer GÜRAKAR (Turkish Journal of Gastroenterology, 2020)
-